Modeling ungrammaticality in optimality theory - Rice, Curt; Blaho, Sylvia (London, England ; Oakville, Connecticut : Equinox Publishing ltd, 2009)
Modeling Ungrammaticality in Optimality Theory presents a collection of papers in phonology and syntax on the topic of ineffability, or absolute ungrammaticality. The papers all contribute new analyses of carefully presented cases, making the book useful for researchers exploring ineffability from any theoretical perspective. The theoretical context for the papers is the analytical challenge which these cases present for Optimality Theory.
Cover; Contents; Chapter 1; PART I; Chapter 2; Chapter 3; Chapter 4; PART II; Chapter 5; Chapter 6; Chapter 7; PART III; Chapter 8; Chapter 9; Language index; Author index
Includes bibliographical references and indexes.
Print version record.
Keywords: Speech errors; Grammaticality (Linguistics); Language and languages -- Study and teaching -- Error analysis; Optimality theory (Linguistics); LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax; Grammaticality (Linguistics); Language and languages -- Study and teaching -- Error analysis; Optimality theory (Linguistics); Speech errors; Electronic books; Electronic books